Improving The Standard Of Living Of Oil Palm Farmers With A Shade-Tolerant Chili Planting System In The TM Phase - Kamsia Sitanggang; Siti H Hartati Yusida Saragih; Junita Lubis (Universitas Veteran Bangun Nusantara, 2025)
ABSTRACT Technological advances in agriculture continue to develop, especially in land optimization. One of these technologies is the development of shade-tolerant plants. This technology is widely used in crop diversification programs such as oil palm plants and shade-tolerant chili plants. Palm oil is a plant that has wide spacing, making it possible to optimize land by planting shade-tolerant chili plants. Chili is a crop that has economic value that can increase finances if the cultivation techniques and farming analysis are appropriate. Planting shade-tolerant chilies can increase finances for oil palm farmers, especially in the young TM phase of oil palm plants. This community service aims to provide education to oil palm farmers about efforts to increase their financial income by utilizing the spacing of oil palm plants planted with shade-tolerant chili plants as well as improving their farming analysis skills. This activity was carried out in Sukaramebaru village, Kualu Hulu subdistrict, North Labuhanbatu district, North Sumatra province. The method used in the community service activities was primary data collection through questionnaires distributed to the community. The questionnaire results showed an increase in public understanding of shade-tolerant plants, land diversification, land optimization, and techniques for planting shade-tolerant chilies. Keywords: shade tolerant chilies, land optimization, oil palm farmers